KREATIVITAS DAN KEAKTIFAN GURU FIKIH DALAM MEMBANGUN KETERAMPILAN BELAJAR SISWA KELAS VIII DI MADRASAH TSANAWIYAH NEGERI BATU - Dewi Roikhatul Janah; Muhammad Fahmi Hidayatullah; Ari Kusuma Sulyandari (VICRATINA, 2022)
This research was conducted with the aim of  describes how creativity and activation of fikih teacher VIII class in building their student skill through learning in MTs Negeri Batu. This research uses qualitative methods approach, and data collection through observation methods, interviews, and documentation. This result of the research that has been carried out are (1) fikih teachers have creativity in designing teaching materials in the form of learning videos and modules, (2) fikih teacher activities in organizing learning, and (3) fikih teacher creativity and activation in designing assessments to build students learning skills.Kata Kunci: Creativity, Activation, Fikih Teacher, and Learning Skill.